EDUKASI ASUHAN KEBIDANAN IBU NIFAS DALAM PELAYANAN CONTINUITY OF CARE PADA ERA PANDEMI COVID-19 DI SUMATERA BARAT - Yulizawati Yulizawati; Lusiana El Sinta Bustami; Erda Mutiara Halida; Fitrayeni Fitrayeni; Rafika Oktova; Laila Rahmi; Ulfa Farrah Lisa; Aldina Ayunda Insani; Uliy Iffah; Feni Andriani; Miranie Safaringga (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
The postpartum period is an important period for health workers to always monitor to avoid complications during the puerperium. Improper implementation can increase the Maternal Mortality Rate (MMR). During this pandemic, pregnant and breastfeeding women are categorized as vulnerable to Covid-19 corona virus infection because they have low immunity due to hormonal changes. As of June 4, 2020, there were 594 positive cases of Covid-19 for the West Sumatra region, 25 people died and 312 people recovered. There is a need for the role of health workers and the education department, husband's involvement and family participation with sustainable midwifery care. the method is carried out by interviewing and providing online and contact care according to the health protocol from the ministry of health. The application of the model of continuous care (Continuity of Care) is given since pregnancy, birth and the postnatal period for all women, both low and highrisk mothers and in all series of midwifery units in West Sumatra. The results of the activity showed that the awareness of mothers, husbands and families to be able to provide assistance and implementation of the fulfillment of the physical and psychological needs of mothers during childbirth by paying attention to environmental conditions in this Covid-19 pandemic era. Evaluation of midwifery care until the end of the puerperium needs to be carried out in order to assess better postpartum outcomes and the achievement of exclusive breastfeeding.